2021
DOI: 10.1016/j.celrep.2021.108903
|View full text |Cite
|
Sign up to set email alerts
|

The DEAD-box helicase DDX56 is a conserved stemness regulator in normal and cancer stem cells

Abstract: Across the animal kingdom, adult tissue homeostasis is regulated by adult stem cell activity, which is commonly dysregulated in human cancers. However, identifying key regulators of stem cells in the milieu of thousands of genes dysregulated in a given cancer is challenging. Here, using a comparative genomics approach between planarian adult stem cells and patient-derived glioblastoma stem cells (GSCs), we identify and demonstrate the role of DEAD-box helicase DDX56 in regulating aspects of stemness in four st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 105 publications
1
14
0
Order By: Relevance
“…DDX56 has also been reported to regulate ribosome assembly through its association with the Oct4 and Sox2 complex, which is necessary to maintain embryonic stem cells (ESCs) proliferation [ 91 ]. DDX56 is upregulated in osteosarcoma and colorectal cancer ( Table 1 ) [ 92 , 93 , 94 ]. Depletion of the DDX56 arrest cell cycle in the G2/M phase via the decrease of tumor suppressor WEE1 expression, which functions as a G2/M DNA damage checkpoint ( Figure 3 ) [ 94 ], results in the inhibition of cell proliferation and clone formation and the induction of p53 mediated apoptosis in osteosarcoma cells [ 92 , 93 ].…”
Section: The Role Of Rna Helicases In Regulation Of Cell Cycle Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…DDX56 has also been reported to regulate ribosome assembly through its association with the Oct4 and Sox2 complex, which is necessary to maintain embryonic stem cells (ESCs) proliferation [ 91 ]. DDX56 is upregulated in osteosarcoma and colorectal cancer ( Table 1 ) [ 92 , 93 , 94 ]. Depletion of the DDX56 arrest cell cycle in the G2/M phase via the decrease of tumor suppressor WEE1 expression, which functions as a G2/M DNA damage checkpoint ( Figure 3 ) [ 94 ], results in the inhibition of cell proliferation and clone formation and the induction of p53 mediated apoptosis in osteosarcoma cells [ 92 , 93 ].…”
Section: The Role Of Rna Helicases In Regulation Of Cell Cycle Progressionmentioning
confidence: 99%
“…DDX56 is upregulated in osteosarcoma and colorectal cancer ( Table 1 ) [ 92 , 93 , 94 ]. Depletion of the DDX56 arrest cell cycle in the G2/M phase via the decrease of tumor suppressor WEE1 expression, which functions as a G2/M DNA damage checkpoint ( Figure 3 ) [ 94 ], results in the inhibition of cell proliferation and clone formation and the induction of p53 mediated apoptosis in osteosarcoma cells [ 92 , 93 ]. However, whether DDX56 regulates the cell cycle through p53-p21 signaling needs to be further investigated.…”
Section: The Role Of Rna Helicases In Regulation Of Cell Cycle Progressionmentioning
confidence: 99%
“…The sample size of the patient models was relatively small in a single center. Although DDX56 is enriched primarily in the nucleolus, it disperses throughout the cytoplasm upon treatment with cytotoxic agents [ 42 ]. This phenotype predicts that DDX56 may have different functions in different cellular organelles.…”
Section: Discussionmentioning
confidence: 99%
“…The DDX family contains 12 highly conserved motifs and can be easily identified by the inclusion of special DEAD (ASP-Glu-Ala-ASP) motifs. These highly conserved DDX RNA helicases are necessary for almost all aspects of the RNA metabolism process, from RNA transcription to degradation [6][7][8][9]. Recently, emerging evidence has showed that DDX helicases can act as sensors, regulators and/or effectors during viral infections [10,11], implicating the diverse roles of these DDX helicases.…”
Section: Introductionmentioning
confidence: 99%